Mites associated with blackberry (Rubus sp. cv. Tupy) in two areas of Michoacan, México. (2019)
Damage caused by phytophagous mites is one of the main phytosanitary problems on blackberry crop. The mite species identification is a very significant activity to implement a program of integrated pest management. The aim of this study was to identify the species of phytophagous mites, predators, and other mites associated with blackberry crop in two locations of Michoacan, Mexico. The research was performed in two blackberry orchards located at Ziracuaretiro and Tacambaro municipalities, which had different type of management: conventional and non-conventional, respectively. In each orchard, 18 samples were collected at 15 d-intervals during an annual cycle, from June 2015 to May 2016. The collected mites were mounted in permanent slide for their taxonomic determination with specific keys with specific keys. Seventeen mite species belonging to ten families were identified, which six were phytophagous species, six were predatory, and five had varied habits. Six of the 17 taxa identified are new records of mites associated with blackberry crop. Most of the mites were collected in the conventional crop (65.4 %), while the abundance of predator mites was highest in the no-conventional crop.